Early heme oxygenase 1 induction delays tumour initiation and enhances DNA damage repair in liver macrophages of Mdr2−/− mice. Issue 1 (December 2018) - Barikbin, Roja; Berkhout, Laura; Bolik, Julia; Schmidt-Arras, Dirk; Ernst, Thomas; Ittrich, Harald; Adam, Gerhard; Parplys, Ann; Casar, Christian; Krech, Till; Karimi, Khalil; Sass, Gabriele; et al.
Abstract Multi drug resistance protein 2 knockout mice (Mdr2 −/− ) are a mouse model of chronic liver inflammation and inflammation-induced tumour development. Here we investigated the kinetics of early heme oxygenase 1 (HO-1) induction on inflammation, tumour development, and DNA damage inMdr2 −/− mice. HO-1 was induced by intraperitoneal injection of cobalt protoporphyrin IX (CoPP) twice weekly for 9 consecutive weeks. Immediately after HO-1 induction, liver function improved and infiltration of CD4+ and CD8+ T cells was reduced. Furthermore, we observed increased p38 activation with concomitant reduction ofCyclin D1 expression in agedMdr2 −/− mice. Long-term effects of HO-1 induction included increased CD8+ T cell infiltration as well as delayed and reduced tumour growth in one-year-old animals. Unexpectedly, DNA double-strand breaks were detected predominantly in macrophages of 65-week-oldMdr2 −/− mice, while DNA damage was reduced in response to early HO-1 inductionin vivo andin vitro . Overall, early induction of HO-1 inMdr2 −/− mice had a beneficial short-term effect on liver function and reduced hepatic T cell accumulation. Long-term effects of early HO-1 induction were increased CD8+ T cell numbers, decreased proliferation as wells as reduced DNA damage in liver macrophages of aged animals, accompanied by delayed and reduced tumour growth.